Long-term survival and success of resin-bonded fixed partial dentures with hybrid versus conventional retainers - Handermann, Rebecca; Rammelsberg, Peter; Bömicke, Wolfgang (The journal of prosthetic dentistry, 2025)
Statement of problem - Hybrid resin-bonded fixed partial dentures (RBFPDs) may be considered for single-tooth edentulous spaces as part of a defect-oriented, minimally invasive treatment approach, though clinical data, especially concerning observation time, are limited. - Purpose - The purpose of this clinical study was to compare the long-term survival of metal-ceramic RBFPDs with a conventional wing-wing retainer design (cRBFPDs) and RBFPDs with a mixed retainer design (mRBFPDs) combining adhesive wings and crowns or partial crowns as retainers. - Material and methods - Eighty-nine participants received 62 cRBFPDs and 32 mRBFPDs (n=22, adhesive wing and crown; n=10, adhesive wing and partial crown). Clinical follow-ups were performed within 6 weeks of adhesive cementation and annually thereafter. The mean ±standard deviation observation time of the restorations was 8.1 ±5.1 years. The cumulative RBFPD survival, success, and debonding-free survival were calculated for each group according to the Kaplan-Meier method. A log-rank test assessed survival distribution equality, and Cox regression analyzed variable effects on complications (α=.05 for all tests). - Results - For cRBFPDs, survival was 100% at 5 years and 89.8% at 10 years. For all mRBFPDs, survival was 92.9% at 5 years and 75.4% at 10 years (log-rank, P=.038). Success of cRBFPDs was 94.4% at 5 years and 75.4% at 10 years. For mRBFPDs, success was 82.3% at 5 years and 64.2% at 10 years (P=.387). Survival without debonding was 94.4% at 5 years and 82.4% at 10 years for cRBFPDs. For mRBFPDs, debonding-free survival was 89.6% at 5 years and 79.8% at 10 years (log-rank, P=.998). The Cox-regression analysis showed that the variables sex (P=.995), location (P≥.888), jaw (P=.213), retainer design (P≥.816), and adhesive luting system (P≥.600) had no statistically significant effect on the incidence of complications in the RBFPDs. In contrast, the use of dental dam (P=.046) and nonvital teeth (P≤.001) had a statistically significant effect on the incidence of complications. - Conclusions - RBFPDs with a hybrid retainer design showed acceptable long-term clinical performance.
Online verfügbar: 14. Mai 2025, Artikelversion: 02. September 2025
Gesehen am 14.01.2026